PENGARUH AKUNTABILITAS, TRANSPARANSI, DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN ALOKASI DANA DESA - Nada Salsabila Ramadhani; Anik Yuliati (Jurnal Proaksi, 2021)
This study aims to examine the effect of accountability, transparency, and social participation on the management of village fund allocations in villages in the Kalitidu sub-district, Bojonegoro district. The subjects of this research are village officials who directly manage the allocation of village funds. The method of determining the sample used purposive sampling technique, so that a sample of 72 village officials was obtained. Data were collected through a questionnaire. Data were analyzed using SEM PLS with WarpPLS 7.0 software program. The results of the study prove that accountability, transparency, and social participation had a positive and significant impact on the management of village fund allocations.